RODA PUTAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA DI SD - ROHMAH, ERWIN RAHAYU SAPUTRA, MITA MIFTAHUR (Wahana Sekolah Dasar, 2021)
Learning media is a teaching aid or the like, this was stated by Erman Suherman who classified media into two parts, namely media as a carrier of information (science), and media which was also a tool for embedding concepts such as educational props. mathematics. This rotary wheel is one of the teaching aids which was developed to help the learning process of children, especially in elementary schools. The rotary wheel is used to make it easier for children to memorize formulas, shapes and other shapes.